Incidental Renal Botryomycosis in a Nonfunctioning Kidney - Mary Mathew; Bhavna Nayal; Bhawna Nagel; Joseph Thomas (Case Reports in Nephrology)
Botryomycosis is a unique form of bacterial infection, closely mimicking actinomycosis. The usual site of occurrence is the skin and renal botryomycosis is very rare. The most common organism is Staphylococcus aureus which can be identified using Gram stain and confirmed by culture. Early and accurate diagnosis can ensure appropriate antibiotic therapy. We present a young lady diagnosed to have incidental botryomycosis of the kidney, following nephrectomy.